Impact of male migration of contraceptive use, unmet need, and fertility in Nepal: Further analysis of the 2011 Nepal Demographic and Health Survey - Khanal, Mukti Nath; Shrestha, Dirga Raj; Pant, Prakash Dev; Mehata, Suresh (DHS Further Analysis Reports No. 74, 2013)
Despite political instability, armed conflict, poor economic status, and difficulty in accessing health services, Nepal has made considerable progress in improving reproductive health over the last two decades. There has been substantial progress in reducing maternal mortality, under-five mortality, and the total fertility rate (TFR). Nepal is on track to meet Millennium Development Goals (MDG) 4 (reducing child mortality rates) and 5 (improving maternal health), and has even received international awards such as the Global Alliance for Vaccines and Immunization (GAVI) award in 2009 for reducing child mortality, the MDG Summit award in 2010 for reducing maternal mortality, and the Resolve award from the Global Leaders Council for Reproductive Health in 2012 for improving maternal and neonatal health (WHO and UNICEF, 2012). Despite these gains, Nepal’s progress on MDG 5b, universal access to reproductive health, as measured by the contraceptive prevalence rate (CPR) and by the level of unmet need for family planning, appears to have slowed. Such evidence raises the question, why has fertility declined so rapidly in Nepal despite stagnation of contraceptive prevalence? This paper examines whether patterns in male migration can help account for the surprising decline in fertility in Nepal despite a stall in the uptake of contraceptives between 2006 and 2011. Nepal has a long history of labor migration, both internal and international (Sharma and Sharma, 2011). This trend has been increasing over the years, particularly among males. On average, at least 1,099 Nepali migrant workers leave the country every day.
For assistance using downloaded citations from The DHS Program, please visit http://dhsprogram.com/publications/Citing-DHS-Publications.cfm
This report presents findings from a further analysis study undertaken as part of the follow-up to the 2011 Nepal Demographic and Health Survey (NDHS). Funding for the further analysis of the survey was provided by the United States Agency for International Development (USAID), the United Kingdom’s Department for International Development (DFID) and the United Nations Population Fund (UNFPA). ICF International provided technical assistance for the survey and further analysis, and New ERA provided in-country coordination and technical assistance through the MEASURE DHS program, a USAID-funded project providing support and technical assistance in the implementation of population and health surveys in countries worldwide. The opinions expressed herein are those of the authors and do not necessarily reflect the views of USAID or the US government or other funding agencies. This report is part of the MEASURE DHS program, which is designed to collect, analyze, and disseminate data on fertility, family planning, maternal and child health, nutrition, and HIV/AIDS. Additional information about the 2011 NDHS may be obtained from the Population Division, Ministry of Health and Population, Government of Nepal, Ramshahpath, Kathmandu, Nepal; telephone: (977-1) 4262987; and from New ERA, P.O. Box 722, Kathmandu, Nepal; telephone: (977-1) 4423176/4413603; fax: (977-1) 4419562; e-mail: info@newera.com.np. Information about the DHS program may be obtained from MEASURE DHS, ICF International, 11785 Beltsville Drive, Suite 300, Calverton, MD 20705, USA; telephone: 301-572-0200; fax: 301-572-0999; e-mail: reports@measuredhs.com; Internet: http://www.measuredhs.com.